Baltimaade üldlaulupidude laulutraditsioonid ja pärand - Guntis Šmidchens (Mäetagused, 2016)
An overview of all the 1,973 songs that have appeared in seventy Estonian, Latvian, and Lithuanian national song celebration programmes from 1869 to the present day reveals a richly innovative, creative tradition: in each of the three festival repertoires, 74–84 percent of the songs were performed only once over the entire history of the national celebrations. When concert participants choose to repeat songs sung in previous years, they identify these songs as heritage. Sometimes, most notably in the retrospective Estonian programmes of 1969 and 2014, a large portion of the concert repertoire was repeated from the past. The tradition as a whole, however, is not necessarily past-oriented. Some celebrations have turned away from heritage. In the 1928 Estonian celebration, for example, only 2 percent of the programme (only one song) had ever been sung in an earlier celebration. This, too, is a heritage of song celebrations: future organisers are free to decide how many, if any, songs they wish to repeat from earlier festivals. The song festival tradition allows both innovative and conservative choice of repertoire at any given festival.